Rapid Expert Consultation on Archival Data Storage Technologies for the Intelligence Community - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
Member agencies of the intelligence community (IC) collect, maintain, and store large amounts of data. There is a profusion of sensors and communications options that has led to a dramatic escalation in the amount of data readily available for a wide variety of purposes. Much more data are being created than are being deleted. But a large fraction, as much as 30 to 35 percent of enterprise data, is data that are rarely accessed (with weeks to years elapsing between uses) and may sit for a long period of time. This poses a challenge because it means that, worldwide, a massive number of exabytes of data need to be securely maintained, managed, and administered in some sort of way. Additionally, the amount of data that will need to be archived for short- and long-term use will continue to rise. In particular, the IC has the potential to be one of the largest customers for cold data storage because of its wide-ranging need for information. At the request of the Office of the Director of National Intelligence (ODNI), this Rapid Expert Consultation (REC) explores options for technologies for archival data storage, focusing primarily on current data storage technologies, particularly magnetic storage, Flash, MRAM, and optical storage. While not all of these technologies are well suited to archival storage applications, the ODNI indicated a desire to hear about all possible options. Brief overviews of emerging technologies are included. Finally, the REC offers comments on the importance of non-technological aspects of archiving, including policies and personnel, which should be considered in the design and acquisition of long-term data storage systems.
Keywords: Computers and Information Technology; Conflict and Security Issues

The Anthrax Letters: A Medical Detective Story - Cole, Leonard A. (The National Academies Press, 2003)
At 2:00am on October 2, 2001, Robert Stevens entered a hospital emergency room. Feverish, nauseated, and barely conscious, no one knew what was making him sick. It was the doctors and public health officials who solved this medical mystery. Stevens was the first fatal victim of bioterrorism in America.
Keywords: Explore Science; Conflict and Security Issues

Disposal Options for the Rocket Motors From Nerve Agent Rockets Stored at Blue Grass Army Depot - National Research Council (The National Academies Press, 2012)
The Blue Grass Chemical Agent-Destruction Pilot Plant (BGCAPP) is under construction near Richmond, Kentucky, two dispose of one of the two remaining stockpiles of chemical munitions in the United States. The stockpile that BGCAPP will dispose of is stored at the Blue Grass Army Depot (BGAD). BGCAPP is a tenant activity on BGAD.
Keywords: Environment and Environmental Studies; Conflict and Security Issues

Nutrient Composition of Rations for Short-Term, High-Intensity Combat Operations - Institute of Medicine (The National Academies Press, 2006)
Recognizing the importance of good nutrition for physical and mental status, the Department of Defense asked the Institute of Medicine to guide the design of the nutritional composition of a ration for soldiers on short-term, high-stress missions. Nutrient Composition of Rations for Short-Term, High-Intensity Combat Operations considers military performance, health concerns, food intake, energy expenditure, physical exercise, and food technology issues. The success of military operations depends to a large extent on the physical and mental status of the individuals involved. Appropriate nutrition during assault missions is a continuous challenge mainly due to diminished appetites of individuals under stress. Many less controllable and unpredictable factors, such as individual preferences and climate, come into play to reduce appetite. In fact, soldiers usually consume about half of the calories needed, leaving them in a state called "negative energy balance." The consequences of being in negative energy balance while under these circumstances range from weight loss to fatigue to mental impairments. An individual's physiological and nutritional status can markedly affect one's ability to maximize performance during missions and may compromise effectiveness. With the number of these missions increasing, the optimization of rations has become a high priority.
Keywords: Conflict and Security Issues; Food and Nutrition

Review of Report and Approach to Evaluating Long-Term Health Effects in Army Test Subjects - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2018)
Between 1942 and 1975, the U.S. Army conducted tests on human subjects to study the effects of a variety of agents, including chemical warfare agents, biological agents, medications, vaccines, and other substances. The tests investigated the immediate or short-term health effects from acute exposure to understand vulnerabilities to attack. Whether the exposures could have resulted in long-term health consequences to the test subjects has been assessed periodically, and the Army is required to notify subjects of information relating to potential health effects associated with exposure to the test agents. Most recently, a 2016 court injunction directed the Army to provide test subjects with new information about potential long-term health effects associated with their exposures, and to provide medical care if an injury or illness could be attributed to their participation in an Army chemical or biological testing program. In support of the first requirement, the Army contracted a report, Assessment of Potential Long-Term Health Effects on Army Human Test Subjects of Relevant Biological and Chemical Agents, Drugs, Medications and Substances: Literature Review and Analysis (the Report), to determine whether new information published since 2006 should be provided to the veterans.
Keywords: Conflict and Security Issues; Health and Medicine

Assuring the U.S. Department of Defense a Strong Science, Technology, Engineering, and Mathematics (STEM) Workforce - National Academy of Engineering; National Research Council (The National Academies Press, 2012)
The ability of the nation's military to prevail during future conflicts, and to fulfill its humanitarian and other missions, depends on continued advances in the nation's technology base. A workforce with robust Science, Technology, Engineering and Mathematics (STEM) capabilities is critical to sustaining U.S. preeminence. Today, however, the STEM activities of the Department of Defense (DOD) are a small and diminishing part of the nation's overall science and engineering enterprise. Assuring the U.S. Department of Defense a Strong Science, Technology, Engineering, and Mathematics (STEM) Workforce presents five principal recommendations for attracting, retaining, and managing highly qualified STEM talent within the department based on an examination of the current STEM workforce of DOD and the defense industrial base. As outlined in the report, DOD should focus its investments to ensure that STEM competencies in all potentially critical, emerging topical areas are maintained at least at a basic level within the department and its industrial and university bases.
Keywords: Education; Industry and Labor; Conflict and Security Issues

Safety and Security of Commercial Spent Nuclear Fuel Storage: Public Report - National Research Council (The National Academies Press, 2006)
In response to a request from Congress, the Nuclear Regulatory Commission and the Department of Homeland Security sponsored a National Academies study to assess the safety and security risks of spent nuclear fuel stored in cooling pools and dry casks at commercial nuclear power plants. The information provided in this book examines the risks of terrorist attacks using these materials for a radiological dispersal device. Safety and Security of Commercial Spent Nuclear Fuel is an unclassified public summary of a more detailed classified book. The book finds that successful terrorist attacks on spent fuel pools, though difficult, are possible. A propagating fire in a pool could release large amounts of radioactive material, but rearranging spent fuel in the pool during storage and providing emergency water spray systems would reduce the likelihood of a propagating fire even under severe damage conditions. The book suggests that additional studies are needed to better understand these risks. Although dry casks have advantages over cooling pools, pools are necessary at all operating nuclear power plants to store at least the recently discharged fuel. The book explains it would be difficult for terrorists to steal enough spent fuel to construct a significant radiological dispersal device.
Keywords: Conflict and Security Issues; Environment and Environmental Studies

Strengthening Long-Term Nuclear Security: Protecting Weapon-Usable Material in Russia - National Research Council (The National Academies Press, 2006)
In July 2005, the National Academies released the report Strengthening Long-term Nuclear Security: Protecting Weapon-Usable Material in Russia. The report highlighted several obstacles in the transition from a U.S.-Russian cooperative program to a Russian-directed and Russian-funded fully indigenized program that will ensure the security of 600 tons of weapon-usable nuclear material at a level of international acceptability. Overcoming these obstacles requires an increased political commitment at a number of levels of the Russian Government to modern material protection, control, and accounting systems (MPC&A). Adequate resources must be provided to facilities where weapon-usable material is located for upgrading and maintaining MPC&A systems. Additionally, the technical security systems that are being installed through the cooperative program need to be fully embraced by Russian managers and specialists. The report recommends the establishment of a ten-year indigenization fund of about $500 million provided by Russia and its G-8 partners as a new mechanism for gradually shifting the financial burden of MPC&A to the Russian Government.
Keywords: Conflict and Security Issues

Controlling the Quantum World: The Science of Atoms, Molecules, and Photons - National Research Council (The National Academies Press, 2007)
As part of the Physics 2010 decadal survey project, the Department of Energy and the National Science Foundation requested that the National Research Council assess the opportunities, over roughly the next decade, in atomic, molecular, and optical (AMO) science and technology. In particular, the National Research Council was asked to cover the state of AMO science, emphasizing recent accomplishments and identifying new and compelling scientific questions. Controlling the Quantum World, discusses both the roles and challenges for AMO science in instrumentation; scientific research near absolute zero; development of extremely intense x-ray and laser sources; exploration and control of molecular processes; photonics at the nanoscale level; and development of quantum information technology. This book also offers an assessment of and recommendations about critical issues concerning maintaining U.S. leadership in AMO science and technology.
Keywords: Math, Chemistry, and Physics; Conflict and Security Issues

Atoms, Molecules, and Light: AMO Science Enabling the Future - National Research Council (The National Academies Press, 2002)
With the publication in 1994 of Atomic, Molecular, and Optical Science: An Investment in the Future (the FAMOS report), the National Research Council launched the series Physics in a New Era, its latest survey of physics. Each of the six area volumes in the survey focuses on a different subfield of physics, describing advances since the last decadal survey and suggesting future opportunities and directions. This survey culminated in 2001 with the publication of the seventh and final volume, Physics in a New Era: An Overview. Since the publication of the FAMOS report, the developments in atomic, molecular, and optical (AMO) science have been amazing. Significant advances in areas such as cooling and trapping, atom and quantum optics, single-atom and single-molecule detection, and ultrafast and ultra intense phenomena, along with the emergence of new applications, made it clear that an update of the FAMOS report was needed. With support from the National Science Foundation and the Department of Energy, the Committee for an Updated Assessment of Atomic, Molecular, and Optical Science was formed. The committee's statement of task reads as follows: The committee will prepare a narrative document that portrays the advances in AMO science and its impact on society. This report highlights selected forefront areas of AMO science, emphasizing recent accomplishments and new opportunities, identifies connections between AMO science and other scientific fields, emerging technologies, and national needs, describes career opportunities for AMO scientists. To accomplish its task and at the same time reach a broad audience, the committee decided to present its report in the form of a brochure highlighting selected advances, connections, and impacts on national needs. An exhaustive assessment of the field, which will fall within the purview of the next decadal survey, was not the goal of the update. The committee would like to express its gratitude for the informative interactions it had with many scientists and policy makers. Many colleagues completed a questionnaire and suggested topics to be included in this report. The final selection of topics was made in accordance with the criteria set forth in the statement of task. While this report was still being written, the tragic events of September 11, 2001, occurred. AMO science and its applications have already played and will continue to play a central role in our nation's response to terrorist threats from conventional as well as chemical or biological weapons. Some of the technology discussed in this report in the chapter "AMO Science Enhancing National Defense" was used successfully for the U.S. military response in Afghanistan—the Global Positioning System (GPS) and laser-guided munitions are just two examples. AMO science will also enable the development of early detection techniques that will help to neutralize the threat from biological and chemical agents.
Keywords: Math, Chemistry, and Physics; Conflict and Security Issues

Examination of the U.S. Air Force's Science, Technology, Engineering, and Mathematics (STEM) Workforce Needs in the Future and Its Strategy to Meet Those Needs - National Research Council (The National Academies Press, 2010)
The Air Force requires technical skills and expertise across the entire range of activities and processes associated with the development, fielding, and employment of air, space, and cyber operational capabilities. The growing complexity of both traditional and emerging missions is placing new demands on education, training, career development, system acquisition, platform sustainment, and development of operational systems. While in the past the Air Force's technologically intensive mission has been highly attractive to individuals educated in science, technology, engineering, and mathematics (STEM) disciplines, force reductions, ongoing military operations, and budget pressures are creating new challenges for attracting and managing personnel with the needed technical skills. Assessments of recent development and acquisition process failures have identified a loss of technical competence within the Air Force (that is, in house or organic competence, as opposed to contractor support) as an underlying problem. These challenges come at a time of increased competition for technical graduates who are U.S. citizens, an aging industry and government workforce, and consolidations of the industrial base that supports military systems.
Keywords: Education; Conflict and Security Issues; Industry and Labor

Crisis Management in the Nuclear Age - National Academy of Sciences; National Research Council (The National Academies Press, 1987)

Powering the U.S. Army of the Future - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
At the request of the Deputy Assistant Secretary of the Army for Research and Technology, Powering the U.S. Army of the Future examines the U.S. Army's future power requirements for sustaining a multi-domain operational conflict and considers to what extent emerging power generation and transmission technologies can achieve the Army's operational power requirements in 2035. The study was based on one operational usage case identified by the Army as part of its ongoing efforts in multi-domain operations. The recommendations contained in this report are meant to help inform the Army's investment priorities in technologies to help ensure that the power requirements of the Army's future capability needs are achieved.
Keywords: Conflict and Security Issues

Nuclear Proliferation and Arms Control Monitoring, Detection, and Verification: A National Security Priority: Summary of the Final Report - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
Robust monitoring, detection, and verification capabilities are necessary to provide decision makers with critical information regarding nuclear threats and to support deterrence and nonproliferation by uncovering efforts to clandestinely develop a nuclear capability or enhance an existing capability. The United States has significant capabilities to monitor, detect, and verify nuclear weapons and fissile material production in foreign states, but in order to address future challenges and avoid surprises, these capabilities must be strengthened and maintained through research and development and operationalization of new technologies. Congress tasked the National Academies of Sciences, Engineering, and Medicine to undertake an independent review and assessment of the United States capabilities for monitoring, detection, and verification of nuclear weapons and fissile material in the fiscal year 2020 National Defense Authorization Act. The study committee released an extensive interim report in April 2021 after an initial phase of data gathering. Following an additional data-gathering period that included examining restricted information unavailable to the committee during the initial phase of the project, the committee produced a final report in January 2023. In that report, the committee reassessed the findings and recommendations made in its interim report and found them to be supported and confirmed by the additional information. This document, the public summary of the final report, reproduces the findings and recommendations from the interim report and includes the committee’s commentary regarding many of the interim report findings and recommendations after additional data gathering.
Keywords: Conflict and Security Issues

U.S. Army Futures Command Research Program Realignment - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The U.S. Army Futures Command (AFC) leads a continuous effort to modernize and innovate to support future warfighters. AFC now oversees Combat Capability Development Command and has recently reorganized certain research offices, laboratories, and engineering centers. In response to this realignment, the Senate Armed Services Committee asked the National Academies' Board on Army Research and Development to examine these research portfolio changes and assess their impact. This report investigates and assesses the Army's strategy behind the realignment, discusses the issues with stakeholders, and makes recommendations to ensure the alignment meets with Army modernization priorities.
Keywords: Conflict and Security Issues

Global Food Security and Sustainability Implications of the Ukraine Conflict: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On June 1, 2022, the National Academies of Sciences, Engineering, and Medicine convened a public workshop to discuss global food security challenges arising from the Ukraine conflict and possible approaches to address these challenges. The workshop focused on short-term responses to the current crisis, opportunities for international collaborations, and how the crisis could impact U.S. national security interests in a changing climate, including the relationships between agricultural production, climate change, and security. Discussions also addressed connections among areas such as agricultural production, land use, energy, water, health, and biodiversity critical to promoting long term sustainability. This publication highlights the presentations and discussion of the workshop.
Keywords: Conflict and Security Issues

Final Review of the Study on Supplemental Treatment Approaches of Low-Activity Waste at the Hanford Nuclear Reservation: Review #4 - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
The U.S. Department of Energy's Office of Environmental Management is responsible for managing and cleaning up the waste and contamination at the Hanford Nuclear Reservation, the nation's biggest and most complex nuclear cleanup challenge. At the site, 177 underground tanks collectively contain about 211 million liters of waste that includes high-activity and low-activity materials. At the request of Congress, Final Review of the Study on Supplemental Treatment Approaches of Low-Activity Waste at the Hanford Nuclear Reservation: Review #4 focuses on approaches for treatment and disposal of the supplemental portion of the low-activity waste from the tanks. This review report discusses developments since the publication of Review #3 and provides a summary of public comments on the third committee review report. The authoring committee then shares their views on these comments and whether they change any of the findings or recommendations in the third review report.
Keywords: Conflict and Security Issues

Advanced Battle Management System: Needs, Progress, Challenges, and Opportunities Facing the Department of the Air Force - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The U.S. Department of Defense is pursuing an improved ability to more closely integrate and operate jointly against agile adversaries through Joint All-Domain Command and Control (JADC2). This framework will seamlessly integrate sensors, networks, platforms, commanders, operators, and weapon systems for rapid information collection, decision-making, and projection of joint and multinational forces. The Department of the Air Force's contribution to JADC2 is the Advanced Battle Management System (ABMS). As an evolving system in the early stages of definition, ABMS architecture and its supporting elements remain dynamic. Advanced Battle Management System assesses the technical approach being employed by ABMS and its ability to effectively support the range of system integration desired, while also supporting operational and development agility; and the governance being applied by ABMS and if it is appropriate and sufficient to enable quick development and evolution of capabilities while maintaining appropriate government control over the output.
Keywords: Conflict and Security Issues

Performance Metrics for the Global Nuclear Detection Architecture: Abbreviated Version - National Research Council (The National Academies Press, 2013)
The Global Nuclear Detection Architecture (GNDA) is described as a worldwide network of sensors, telecommunications, and personnel, with the supporting information exchanges, programs, and protocols that serve to detect, analyze, and report on nuclear and radiological materials that are out of regulatory control. The Domestic Nuclear Detection Office (DNDO), an office within the Department of Homeland Security (DHS), coordinates the development of the GNDA with its federal partners. Performance Metrics for the Global Nuclear Detection Architecture considers how to develop performance measures and quantitative metrics that can be used to evaluate the overall effectiveness and report on progress toward meeting the goals of the GNDA. According to this report, two critical components are needed to evaluate the effectiveness of the GNDA: a new strategic plan with outcome-based metrics and an analysis framework to enable assessment of outcome-based metrics. The GNDA is a complex system of systems meant to deter and detect attempts to unlawfully transport radiological or nuclear material. The recommendations of Performance Metrics for the Performance Metrics for the Global Nuclear Detection Architecture may be used to improve the GNDA strategic plan and the reporting of progress toward meeting its goals during subsequent review cycles.
Keywords: Conflict and Security Issues

Determining Core Capabilities in Chemical and Biological Defense Science and Technology - National Research Council (The National Academies Press, 2012)
The goal of the U.S. Department of Defense's (DoD's) Chemical and Biological Defense Program (CBDP) is to provide support and world-class capabilities enabling he U.S. Armed Forces to fight and win decisively in chemical, biological, radiological, and nuclear (CBRN) environments. To accomplish this objective, the CBDP must maintain robust science and technology capabilities to support the research, development, testing, and evaluation required for the creation and validation of the products the program supplies. The threat from chemical and biological attack evolves due to the changing nature of conflict and rapid advances in science and technology (S&T), so the core S&T capabilities that must be maintained by the CBDP must also continue to evolve. In order to address the challenges facing the DoD, the Deputy Assistant Secretary of Defense (DASD) for Chemical and Biological Defense (CBD) asked the National Research Council (NRC) to conduct a study to identify the core capabilities in S&T that must be supported by the program. The NRC Committee on Determining Core Capabilities in Chemical and Biological Defense Research and Development examined the capabilities necessary for the chemical and biological defense S&T program in the context of the threat and of the program's stated mission and priorities. Determining Core Capabilities in Chemical and Biological Defense Science and Technology contains the committee's findings and recommendations. It is intended to assist the DASD CBD in determining the best strategy for acquiring, developing, and/or maintaining the needed capabilities.
Keywords: Conflict and Security Issues